If x2 + mx + m is a perfect-square trinomial, which equation must be true?
x2 + mx + m = (x – 1)2
x2 + mx + m = (x + 1)2
x2 + mx + m = (x + 2)2
x2 + mx + m = (x + 4)2

Respuesta :

x^2 +mx +m = (x+2 )^2
since (x+2)^2 = x^2 +2(2x) + 2^2
= x^2 + 4x + 4
therefore the answer is m= 4
C

for [tex]1x^2+bx+c[/tex] to be a perfect square trinomial, [tex]c=(\frac{b}{2})^2[/tex]


or [tex]x^2+mx+m[/tex]

thereore, [tex]m=(\frac{m}{2})^2[/tex]

[tex]m=\frac{m^2}{4}[/tex]

4m=m²

m²-4m=0

(m)(m-4)=0

m=0 and m-4=0

m=0 and m=4


so you could have

x²+0x+0=(x-0)²

or

x²+4x+4=(x+2)²


answer is 3rd optio, (x+2)²